Pengaruh Perbandingan Tepung Kacang Tolo Merah (Vigna Angularis) dan Tepung Talas Kimpul (Xanthosoma Sagittifolium) Terhadap Karakteristik Flakes - Monica Elicia Debora Marbun; I Putu Suparthana; Ni Wayan Wisaniyasa (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Abstract Flakes are a breakfast product in the form of thin crumbs with a crunchy texture and rich carbohydrate content. Flakes are generally made from cereals. Utilization of cocoyam flour can be used as an alternative because it is rich in carbohydrates. Kimpul taro flour has a low protein content, so it is necessary to add adzuki bean flour to increase the protein of the flakes. This study aims to determine the effect of the ratio of cocoyam taro flour and adzuki bean flour on the characteristics of flakes and determine the right ratio to produce flakes with the best characteristics. This study used a completely randomized design (CRD) with the treatment of the ratio of cocoyam flour and adzuki bean flour consisting of 5 levels, namely: 100:0, 75:25, 50:50, 25:75, 0:100. All treatments were repeated 3 times, resulting in 15 experimental units. The data obtained were analyzed with variance analysis and in treatments that significantly influenced the treatment, followed by Duncan Multiple Range Test (DMRT). The results showed that the comparison of cocoyam taro flour and adzuki bean flour in flakes had a very significant effect (P<0.01) on moisture content, ash content, protein content, fiber content, crispness in milk sensory color, aroma, taste, texture and overall acceptance and scoring of color, smell, and texture. The treatment of 50% cocoyam taro flour and 50% adzuki bean flour produced flakes with the best characteristics with a moisture content of 2.4%, ash content of 3.03%, protein content of 12.37%, crude fiber content of 4.59%, crispness resistance in milk is 4.3 minutes, the color was cream and liked, the aroma was red beans and cocoyam and liked, the taste liked, the texture was crispy and liked, and overall acceptance liked. Keywords: flakes, the composition of adzuki bean flour and cocoyam flour Abstrak Flakes adalah produk sarapan berbentuk remahan tipis dengan tekstur renyah dan tinggi karbohidrat. Flakes umumnya terbuat dari serealia. Pemanfaatan tepung talas kimpil dapat dijadikan sebagai alternatif karena kaya akan karbohidrat. Tepung talas kimpul memiliki kandungan protein yang rendah, sehingga perlu adanya penambahan tepung kacang tolo merah guna meningkatkan protein flakes. Penelitian ini bertujuan untuk mengetahui pengaruh perbandingan tepung talas kimpul dan kacang tolo merah terhadap karakteristik flakes dan menentukan perbandingan yang tepat untuk menghasilkan flakes dengan karakteristik terbaik. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan perlakuan perbandingan tepung talas kimpul dan tepung kacang tolo merah yang terdiri dari 5 taraf, yaitu: 100:0, 75:25, 50:50, 25:75, 0:100. Seluruh perlakuan diulang sebanyak 3 kali sehingga diperolah 15unit percobaan. Data yang diperoleh dianalisis dengan Anova dan pada perlakuan yang berpengaruh nyata perlakuan, dilanjutkan dengan Duncan Multiple Range Test (DMRT). Hasil penelitian menunjukkan bahwa perbandingan tepung talas kimpul dan tepung kacang tolo merah pada flakes berpengaruh sangat nyata (P<0,01) terhadap kadar air, kadar abu, kadar protein, kadar serat, kerenyahan dalam susu sensoris warna, aroma, rasa, tekstur dan penerimaan keseluruhan serta skoring terhadap warna, aroma, dan tekstur. Perlakuan perbandingan tepung talas kimpul 50% dan tepung kacang tolo merah 50% menghasilkan flakes dengan karakteristik terbaik dengan nilai kadar air 2,4 %, kadar abu 3,03 %, kadar protein 12,37%, kadar serat kasar 4,59%, ketahanan kerenyahan dalam susu 4,3 menit, sensoris warna krem disukai, aroma khas kacang merah dan talas kimpul disukai, rasa disukai, tekstur renyah disukai dan penerimaan keseluruhan disukai. Kata kunci: flakes, komposisi tepung talas kimpul dan tepung kacang tolo merah